The Vertical Profile of Nitrate in the Lacustrine and Transition Zone Koto Panjang Reservoir Kampar District Riau Province - Sihotang, Simon Duce; H, Asmika; Sihotang, Clemens (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was carried out in the lacustrine and transition zone of Koto Panjang Reservoir from October - December 2013. Objective of the present research was to find out the vertical profile of nitrate in this reservoir. The research used survey method, samples were taken horizontally in four stations and vertically in five sampling points. The parameters of water quality measured were nitrate, dissolved oxygen (DO), pH, transparancy, temperature and depth. In the lacustrine zone concentration of nitrate in the surface was 0,148 – 0,166 mg/l, in the 2 Secchi depth was 0,16 – 0,168 mg/l, in the 4 Secchi depth was 0,153 – 0,162 mg/l, in the 12 m depth was 0,158 – 0,166 mg/l and in the bottom was 0,17 – 0,192 mg/l. In the transition zone concentration of nitrate in the surface was 0,1525 – 0,155 mg/l, in the 2 Secchi depth was 0,157 – 0,158 mg/l, in the 4 Secchi depth was 0,158 – 0,175mg/l, and in the bottom was 0,176 – 0,185mg/l. The concentration of dissolved oxygen (DO) was in the range of 0,10 – 8,75 mg/l. The value of pH was in the range of 5,4 – 5,9. Transparancy was in the range of 83,8 – 105 cm. Temperature was in the range of 28 – 32,3 oC. Depth was in the range of 9,3 – 22,7 m. The vertical profile of nitrate in the lacustrine and transition zone Koto Panjang reservoir of the present reseach revealed that nitrate concentration in the transition zone was relatively lower than that of lacustrine in the surface layer of the water, but the pattern of vertical nitrate profile in each zone was similar in which it increased with increasing depth. The parameters of water quality were observed still sustained the aquatic organism life.Keywords: nitrate, the vertical profile, PLTA Koto Panjang Reservoir